Power quality enhancement using active power filter five-level cascade H-bridge under unbalanced and distorted grid - Guergah, Manel; Nebti, Khalil; Rezgui, Salah Eddine; Benalla, Hocine; Ould-Abdeslam, Djaffar Ouid (Національний технічний університет "Харківський політехнічний інститут", 2023)
Introduction. To improve the power quality of a supply system, the total harmonic distortion (THD) is the most important parameter in the quantification of harmonics caused by nonlinear loads. In practice, it must be less than 5 %. The novelty of the proposed work consists in the use of a cascaded five level active filter, when the converter consisting of six H-bridge pairs, each one includes four transistors. Purpose. To increase the efficiency of this filter, two techniques for quantification of harmonic currents are proposed, first the PQ-theory which is simple but can only be used in case of a balanced grid, and second the synchronous reference frame theory (SFR-theory), which is capable of creating harmonic current not only in an unbalanced grid, but also in an unbalanced and distorted beam. Methods. Using the control techniques, the harmonic current is extracted from load current and considered as a reference. The constructed current should follow this reference. Results. The estimation of the active and reactive powers is based on the measurement of the currents crossing the load and the network voltages, these powers are used to determine the shape of the harmonic (reference) current. Using the PI regulator, the output current of the five-level inverter follows the reference current perfectly. The inverters output current is injected into the grid to eliminate harmonic currents. Practical value. In practice, the harmonic distortion rate THD is the most widely used criterion for criticizing the waveform of the currents and judging the quality of the energy involved. For currents on the source side, the THD is considered acceptable if it is less than 5 %, in our proposal the THD is 0.85 % with the PQ-theory and 2.34 % with SFR-theory, so it is optimal.

Вступ. Для поліпшення якості електроенергії у системі електропостачання загальне гармонічне спотворення (ЗГС) є найважливішим параметром кількісної оцінки гармонік, викликаних нелінійними навантаженнями. На практиці вона має бути меншою за 5 %. Новизна запропонованої роботи полягає у використанні каскадного п'ятирівневого активного фільтра, коли перетворювач складається з шести пар Н-мостів, кожна з яких включає чотири транзистора. Мета. Щоб підвищити ефективність цього фільтра, пропонуються два методи кількісного визначення гармонійних струмів: по-перше, PQ-теорія, яка проста, але може використовуватися лише у разі збалансованої сітки, і, по-друге, теорія синхронної системи відліку (теорія SFR), який здатний створювати гармонійний струм не тільки в несиметричній сітці, а й у несиметричному та спотвореному пучку. Методи. Використовуючи методи управління, гармонійний струм витягується зі струму навантаження і розглядається як опорний. Побудований струм повинен слідувати за цим посиланням. Результати. Оцінка активної та реактивної потужностей заснована на вимірюванні струмів, що проходять через навантаження, та мережевих напруг, за цими потужностями визначається форма гармонійного (опорного) струму. При використанні ПІ-регулятора вихідний струм п'ятирівневого інвертора точно відповідає опорному струму. Вихідний струм інвертора подається до мережі для усунення гармонійних струмів. Практична цінність. Насправді коефіцієнт гармонійних спотворень ЗГС є найбільш широко використовуваним критерієм для критики форми хвилі струмів та оцінки якості задіяної енергії. Для струмів на стороні джерела ЗГС вважається прийнятним, якщо він менше 5 %, за нашою пропозицією ЗГС становить 0,85 % з PQ-теорією і 2,34 % з SFR-теорією, тому він є оптимальним.
Keywords: multilevel active power filter; total harmonic distortion; instantaneous active and reactive power; harmonic currents; synchronous reference frame theory; багаторівневий фільтр активної потужності; повні гармонічні спотворення; миттєва активна та реактивна потужності; гармонічні струми; синхронна теорія системи відліку